Pharmacophore, Similarity and ADMET Screening of Casein Kinase 1 inhibitors in Alzheimer's Disease - Rodrigues, R. P.; Silva, C.H.T.P. (Current Bioactive Compounds, 2013)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by marked atrophy of cortex and loss of cortical and subcortical neurons. At least two Casein Kinase 1 isoforms have been implicated in the pathogenesis of AD. The ligand-based virtual screening (LBVS) technique uses the information of a set of actives, focusing on the activity of this group of molecules against the desired target. Generally, this type of technique is used when there is no information on the three dimensional structure of the target. However, the use of LBVS allied with three-dimensional information of the protein binding site provides a more accurate screening, since the information of the active site is taken into account during the analysis of results.
Keywords: Alzheimer